1996
DOI: 10.1111/j.1475-6811.1996.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles and other predictors of relationship satisfaction in dating couples

Abstract: A sample of 186 dating couples completed questionnaires in order to examine thc relevancc o f attachmen1 styles, romantic beliefs, self-esteem, and gender roles to relationship satisfaction. Thc aim was to assess whether male and female anxiety over abandonment and comfort with closencss, and interactions among them, predicted satisfaction beyond the contribution of the other variables. IJsing multiple-regression analysis, it was found that attachment styles successfully predicted satisfaction, after controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 67 publications
7
37
0
2
Order By: Relevance
“…However, other studies reported only partial evidence, or no evidence at all, for partner effects. Using a sample of dating couples, Jones and Cunningham (1996) did not find a partner effect. Murray, Holmes, and Griffin (1996b) examined a sample of young adults and found that women's self-esteem but not men's self-esteem had a partner effect.…”
Section: Self-esteem and Romantic Relationshipsmentioning
confidence: 99%
“…However, other studies reported only partial evidence, or no evidence at all, for partner effects. Using a sample of dating couples, Jones and Cunningham (1996) did not find a partner effect. Murray, Holmes, and Griffin (1996b) examined a sample of young adults and found that women's self-esteem but not men's self-esteem had a partner effect.…”
Section: Self-esteem and Romantic Relationshipsmentioning
confidence: 99%
“…It provides a perspective for understanding individual differences in the degree to which people are comfortable with intimacy (Fraley and Shaver 2000). Adult attachment styles have been shown to influence aspects of psychological well-being, such as relationship satisfaction (Jones and Cunningham 1996;Meyers and Landsberger 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Gender is especially an important variable to investigate in future research. Past research has suggested there are gender differences and much of this can be due to different cultural sex roles (Feldman et al, 1998;Jones & Cunningham, 1996). However, Feldman et al (1998) found a strong reduction in gender differences due to families becoming more accept ing of androgynous behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, fearful attachment occurs when both anxiety and avoidance are high (Brennan et al, 1998). Attachment has been an excellent predictor of relationship satisfaction in both men and women (Jones & Cunningham, 1996), and attachment style during adulthood is influenced by parentchild attachment patterns (e.g., Smith & Ng, 2009). …”
Section: Attachment Theorymentioning
confidence: 99%